Molecular-genetic markers of the oral mucositis development in squamous cell cancer patients - Eugeniya N. Gvozdikova, Anatoliy M. Avanesov, (Opción, 2019)
The aim of the study is to investigate molecular-genetic markers of oral mucositis development in squamous cell cancer patients. Combined and complex treatment of patients with oral mucous layer cancer was performed according to the standards of treatment of malignant neoplasms as a method. The results of the hybridization were registered with a universal hardware and software complex (UAPC) for the analysis of the images obtained from the diagnostic microarrays. In conclusion, oral mucositis remains one of the most serious and often registered complications after antitumor therapy that significantly decreases the quality of life of oncologic patients.